The pediatric doctor’s knowledge on oral health promotion in first infancy in family health basic units - Savi Guisso, Sarita; Consalter Geib, Lorena Teresinha (O Mundo da Saúde, 2007)
Aiming to describe the knowledge pediatric doctors of two cities of Rio Grande do Sul State have concerning oral health in first infancy, this exploratory-descriptive research was done which has a qualitative approach. It had as subjects five pediatric doctors from two cities of Rio Grande do Sul State working in the Family Health Program. Data were collected in July 2006 by means of a questionnaire with open questions. The analyzed contents were grouped in the following categories: 1) pediatric doctor’s knowledge concerning children oral health and 2) implementation of recommended actions by the pediatric doctor. The participants showed a basic level of knowledge on oral health in infancy, but the adopted behaviors not always were compatible with this knowledge, denoting inefficacious actions. The inadequacy of information given to parents and children suggests the necessity of a greater interaction of doctors with dental professionals.